Modulation of the photoluminescence in carbon dots through surface modification: from mechanism to white light-emitting diodes. (13th April 2018) - Zhu, Jinyang; Shao, He; Bai, Xue; Zhai, Yue; Zhu, Yongsheng; Chen, Xu; Pan, Gencai; Dong, Biao; Xu, Lin; Zhang, Hanzhuang; Song, Hongwei
Abstract: Carbon dots (CDs) have emerged as a new type of fluorescent material because of their unique optical advantages, such as high photoluminescence quantum yields (QYs), excellent photo-stability, excitation-dependent emissions, and low toxicity. However, the photoluminescence mechanism for CDs remains unclear, which limits their further practical application. Here, CDs were synthesized via a solvothermal route from citric acid and urea. Through the oxidation and reduction treatment of pristine CDs, the origin of the photoluminescence and the involved mechanism were revealed. We found that the blue/green/red emissions originated from three diverse emitting states, i.e. the intrinsic state, and C=O- and C=N-related surface states, respectively. Based on the as-prepared CDs, a pH sensor depending on the radiometric luminescence detection was developed. Furthermore, we constructed CD/PVP (PVP, polyvinylpyrrolidone) composite films, which exhibited white light emission with photoluminescence QYs of 15.3%. The white light emission with different correlated color temperatures (CCTs), from 4807 K to 3319 K, was obtained by simply changing the amount of PVP solution. Benefiting from the white light-emitting solid-state films, single-component white light-emitting diodes were fabricated with an average color rendering index value (Ra) of 80.0, luminous efficiency of 10.2 lm W −1, and good working stability, thus indicating a promising potential for practical lighting applications.